질소비료 시비량에 따른 들잔디의 생육반응 - 배은지(Eun-Ji Bae); 한정지(Jeong-Ji Han); 이광수(Kwang-Soo Lee); 박용배(Yong-Bae Park); 최수민(Su-Min Choi) (Weed & turfgrass science, 2015)
This study was conducted to find out the optimum nitrogen fertilization for production of good quality and high yield zoysiagrass (Zoysia japonica Steud.), the changes in chemical properties of soil in pot and field experiments treated with different levels of nitrogen fertilizer. In pot experiment, the fresh and dry weights of shoots and stolons and the number of shoots increased as nitrogen levels increased, and showed no significant between 24 and $48kg\;N\;10\;a^{-1}$. In field experiment, the shoot length, fresh and dry weights of shoots, roots and stolons, the number of shoots and total stolons length linearly increased as affected by increased nitrogen application, and were not significantly different between 24 and $32kg\;N\;10\;a^{-1}$. In both experiments, pH and exchangeable cations ($Ca^{2+}$ and $Mg^{2+}$) in soil decreased as the rate of nitrogen application increased. As a results, chemical properties of soil were more deteriorated in the plots of higher nitrogen fertilizer rate. Thus, these results demonstrated that the nitrogen fertilizer rate for maximum growth of zoysiagrass was $24kg\;N\;10\;a^{-1}$ in consideration of growth and soil condition. 양질 다수확 들잔디를 생산하기 위한 적정 질소비료 시비량을 규명하기 위하여 질소 시비량에 따른 들잔디의 생육과 토양화학성의 변화를 알아보고자 와그너 포트시험과 잔디 재배지 포장시험을 수행하였다. 포트시험에서는 지상부와 포복경의 생체중과 건물중, 지상부 개체수는 질소 시비량이 증가함에 따라 증가하였고, 질소비료 시비량 24와 $48kg\;N\;10\;a^{-1}$ 처리구간의 유의한 차이를 보이지 않았다. 잔디재배지 포장시험에서는 질소비료 시비량이 높을수록 지상부길이, 지상부, 포복경과 지하부의 생체중과 건물중, 지상부 개체수와 전체 포복경 개수는 유의성 있게 증가하였으며, 질소비료 $24{\sim}32kg\;N\;10\;a^{-1}$ 처리구간에는 유의한 차이가 없었다. 질소비료 시비량이 증가할수록 토양 내 pH, 치환성 양이온 칼슘과 마그네슘이 낮아져 토양 화학성이 악화되었다. 따라서 들잔디 생육 및 토양의 화학성을 고려한 적정 질소비료 시비량은 $24kg\;N\;10\;a^{-1}$으로 판단되었다.